Posterior versus anterior circulation stroke in young adults: a comparative study of stroke aetiologies and risk factors in stroke among young fabry patients (sifap1) - Sarnowski, Bettina von; Hennerici, Michael G. (Cerebrovascular diseases, 2017)
Background: Although 20-30% of all strokes occur in the posterior circulation, few studies have explored the characteristics of patients with strokes in the posterior compared to the anterior circulation so far. Especially data on young patients is missing. Methods: In this secondary analysis of data of the prospective multi-centre European sifap1 study that investigated stroke and transient ischemic attack (TIA) patients aged 18-55 years, we compared vascular risk factors, stroke aetiology, presence of white matter hyperintensities (WMH) and cerebral microbleeds (CMB) between patients with ischaemic posterior circulation stroke (PCS) and those having suffered from anterior circulation stroke (ACS) based on cerebral MRI. Results: We diagnosed PCS in 612 patients (29.1%, 407 men, 205 women) and ACS in 1,489 patients (70.9%). Their age (median 46 vs. 47 years, p = 0.205) and stroke severity (modified Rankin Scale: both 2, p = 0.375, Barthel Index 90 vs. 85, p = 0.412) were similar. PCS was found to be more frequent among the male gender (66.5 vs. 60.1% with ACS, p = 0.003). Vertebral artery (VA) dissection was more often the cause of PCS (16.8%) than was carotid artery dissection of ACS (7.9%, p < 0.001). Likewise, small vessel disease (Trial of Org 10172 in Acute Stroke Treatment [TOAST] = 3, PCS: 14.7%, ACS: 11.8%) and stroke of other determined aetiology (TOAST = 4, PCS: 24.5%, ACS: 16.0%) were more frequent in those with PCS. Furthermore, patent foramen ovale (PFO; PCS: 31.1%, ACS: 25.4%, p = 0.029) was more often detected in patients with PCS. In contrast, large-artery atherosclerosis (TOAST = 1, PCS: 15.4%, ACS: 22.2%) and cardio-embolic stroke (TOAST = 2, PCS: 15.6%, ACS: 18.0%) were less frequent in those with PCS (p < 0.001) as were preceding cerebrovascular events (10.1 vs. 14.1%, p = 0.014), TIA (4.8 vs. 7.7%, p = 0.016) and smoking (53.2 vs. 61.0%, p = 0.001). The presence, extent, and location of WMH and CMB did not differ between the 2 groups. Conclusions: Our data suggested a different pattern of aetiology and risk factors in young patients with PCS compared to those with ACS. These findings especially call for a higher awareness of VA dissection and potentially for more weight of a PFO as a risk factor in young patients with PCS. Clinical trial registration-URL: http://www.clinicaltrials.gov; NCT00414583.
Gesehen am 09.05.2018